ANALISIS KONTRIBUSI MARGIN UNTUK MENENTUKAN HARGA JUAL OBAT APOTEK EMILIA - Chintia Milla Putri Chintia; Emerensiana Nirma; Maria R S Putri; Nabila Imelda (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The purpose of this study is to analyze the contribution margin to determine the selling price of medicine at Apotek Emilia. The contribution margin is the difference between sales and variable costs, which reflects how much a product contributes to covering fixed costs and generating profit. By understanding the contribution margin, the pharmacy can determine the level of sales needed to achieve profit targets and develop more effective sales strategies. This research uses a quantitative approach by collecting sales data and variable costs from Apotek Emilia over a certain period. The analysis results show that the contribution margin can assist management in making decisions related to sales planning, cost control, and product pricing. The conclusion of this study is that applying contribution margin analysis provides significant benefits in improving the profitability and operational efficiency of the pharmacy.